Robotic Solutions for Air Duct Cleaning: An Overview of Current Research and Applications - Husainy, Avesahemad S. N.; Wagh, Sachin S.; Kore, Shubham V.; Burud, Akash P.; Hajare, Devang G. (Asian Review of Mechanical Engineering, 2022)
According to studies conducted abroad, the HVAC system is to blame for 70% or more of all IAQ problems, and most of these problems are brought on by inadequate system care and maintenance. The lungs of a building, the air ducts, can accumulate deposits of construction grime, dust, tar from cigarettes, insects, smoke and other airborne contaminants. These distribution systems need to be inspected frequently in order to maintain the high efficiency of the air conditioners and lower effect losses. There is evidence that ventilation ducts in HVAC systems can accumulate dust and serve as breeding grounds for microbes even when they are operating normally. The building’s AC duct placement makes it impossible to clean by hand. An assessment of the current state of knowledge and comprehension about the employment of robots for air duct cleaning is what this review paper intends to do. The various varieties of air duct cleaning robots, as well as their capabilities and effectiveness in comparison to more conventional cleaning techniques, will be examined in this study. The cost, effectiveness, and safety of deploying robots to clean air ducts will also be discussed in this study, along with some of their benefits and drawbacks. The review will also look at the state of research and development in the area and identify any potential trends or difficulties in the use of robots for cleaning air ducts in the future. The paper will include a full evaluation of previous research on the subject, including studies, publications, and reports, as well as the methodology employed. The study will include findings and suggestions about the usage of robots for cleaning air ducts for facility managers, researchers, and air duct cleaning specialists. The paper’s overall goal is to present a thorough overview of the status of technology today and some of its prospective air duct cleaning applications.